The metastatic niche formation: focus on extracellular vesicle-mediated dialogue between lung cancer cells and the microenvironment - Pontis, Francesca; Roz, Luca; Fortunato, Orazio; Bertolini, Giulia (Frontiers in Oncology, 2023)
Lung cancer is the deadliest cancer in the world, with the majority of patients presenting with advanced or metastatic disease at first diagnosis. The lungs are also one of the most common sites of metastasis from lung cancer and other tumors. Understanding the mechanisms that regulate metastasis formation from primary lung cancer and in the lungs is therefore fundamental unmet clinical need. One of the first steps during the establishment of lung cancer metastases includes the formation of the pre-metastatic niche (PMN) at distant organs, which may occur even during the early phases of cancer development. The PMN is established through intricate cross-talk between primary tumor-secreted factors and stromal components at distant sites. Mechanisms controlling primary tumor escape and seeding of distant organs rely on specific properties of tumor cells but are also tightly regulated by interactions with stromal cells at the metastatic niche that finally dictate the success of metastasis establishment. Here, we summarize the mechanisms underlying pre-metastatic niche formation starting from how lung primary tumor cells modulate distant sites through the release of several factors, focusing on Extracellular Vesicles (EVs). In this context, we highlight the role of lung cancer-derived EVs in the modulation of tumor immune escape. Then, we illustrate the complexity of Circulating Tumor Cells (CTCs) that represent the seeds of metastasis and how interactions with stromal and immune cells can help their metastatic dissemination. Finally, we evaluate the contribution of EVs in dictating metastasis development at the PMN through stimulation of proliferation and control of disseminated tumor cell dormancy. Overall, we present an overview of different steps in the lung cancer metastatic cascade, focusing on the EV-mediated interactions between tumor cells and stromal/immune cells.